2010
DOI: 10.1007/bf03353634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen on deposition and field emission properties of boron-doped micro- and nano-crystalline diamond films

Abstract: In this paper, we report the effect of nitrogen on the deposition and properties of boron doped diamond films synthesized by hot filament chemical vapor deposition. The diamond films consisting of micro-grains (nano-grains) were realized with low (high) boron source flow rate during the growth processes. The transition of micro-grains to nano-grains is speculated to be strongly (weekly) related with the boron (nitrogen) flow rate. The grain size and Raman spectral feature vary insignificantly as a function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Figure 2(b) shows the XRD patterns of the BND and BDD films. The diffraction peaks at 44.1°, 75.5°, and 91.8° correspond to the (111), (220), and (311) planes of diamond, respectively [17,35,36]. The dominant (111) and (220) peaks denote that the BND and BDD films mainly consist of (111) and (110) orientated grains, which is accordant with the SEM images shown in Figure 1.…”
Section: Morphology and Structure Of Bnd And Bdd Filmssupporting
confidence: 81%
See 1 more Smart Citation
“…Figure 2(b) shows the XRD patterns of the BND and BDD films. The diffraction peaks at 44.1°, 75.5°, and 91.8° correspond to the (111), (220), and (311) planes of diamond, respectively [17,35,36]. The dominant (111) and (220) peaks denote that the BND and BDD films mainly consist of (111) and (110) orientated grains, which is accordant with the SEM images shown in Figure 1.…”
Section: Morphology and Structure Of Bnd And Bdd Filmssupporting
confidence: 81%
“…Noted that for the BND sample, additionally, the broad bands of 1500 cm −1 indicate that the non-diamond carbon mainly comes from the grain boundaries, while the stronger 1500 cm −1 band of the BND film is due to nitrogen atoms preferentially entering the grain boundaries and promoting the formation of sp 2 C-N bonds [35,36]. The broad bands of 2060 cm −1 of the BND film corresponds to N-V 0 formed by the recombination of nitrogen and vacancies [37].…”
Section: Morphology and Structure Of Bnd And Bdd Filmsmentioning
confidence: 99%
“…It can be seen that, besides the noise districts, the three plots go near to a straight line. It indicates that the field emission from the in situ -grown SnO 2 nanowire arrays follows the FN relationship well, and the field emission process is a barrier tunneling quantum mechanical process [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The sharp bands at~1450 and~1525À1550 cm À1 are tentatively interpreted either as modified carbon vibrations produced by nitrogen in the diamond structure (e.g. Li et al, 2009Li et al, , 2010 or as bands produced by other polymorphs of carbon, as observed in shocked graphite and diamond from the Ries crater (e.g. Lapke et al, 2000).…”
Section: Identification Of the Uhp Phases And Textural Relationshipsmentioning
confidence: 99%